Pengaruh Kepuasan Kerja dan Etika Kerja Terhadap Kinerja Melalui Komitmen Organisasi sebagai Variabel Intervening di Dinas Pendidikan Kabupaten Labuhanbatu Utara - Muhammad Arifin, Bahril Datuk, Sjahril Effendy Pasaribu (Journal Economy and Currency Study (JECS), 2022)
The purpose of this study was to determine and analyze the effect of job satisfaction and work ethics on performance through organizational commitment as an intervening variable at the Education Office of North Labuhanbatu Regency, either directly or indirectly. The approach used in this study is an associative approach. The population in this study were 43 employees of the North Labuhanbatu Regency Education Office, while the sample in this study was the 43 employees of the North Labuhanbatu Regency Education Office using a saturated sample. Data collection techniques in this study used interview techniques, documentation studies, observation, and questionnaires. The data analysis technique in this study used path analysis, Hypothesis Testing (t test and F test), and the coefficient of determination. Processing data in this study using the software program SPSS version 22. The results of this study prove that directly job satisfaction and work ethics are significant on performance through organizational commitment as an intervening variable and directly on employees of the North Labuhanbatu Regency Education Office.